Pemanfaatan Pasir Kuarsa Sebagai Lapis Pondasi Jalan - Iriansyah. AS (Jurnal Jalan-Jembatan, 2005)
"Quartz" sand is a potensial resourse as a road material especially in the areas where aggregates are unavailable "Quartz" sand can be found in may areas in Indonesia, but it has not been fully exploited. Concided with the application of asphalt emulsion technology with cold mix, a research has been conducted on "Quartz" sand as subbase with asphalt emulsion mixture as binder (sand base emulsion). "Quarrtz" sand used for research was taken from many areas such as Central Kalimantan, central Sulawesi, and East Java. As comparison to the quality of "Quartz" sand mixture, the sand ex Cimalaka of West Java was used. The test result showed that the mixture, of "Quartz" sand is not significantly different from sand of Cimalaka which has a better quality. Voids is "Quartz" sand mixture were generally bigger than Cimalaka sand, this is due to the nearly uniform gradation of "Quartz" sand. Local "Quartz" sand as subbase material has been experimented in the two km road project of Kasongan - Palataran (km 50 + 000 - 52 + 000) Central Kalimantan. The addition of 1 to 2% of cement can improve the properties of sand base emulsion mixture